2018
DOI: 10.1002/iid3.221
|View full text |Cite
|
Sign up to set email alerts
|

Reactive glia promote development of CD103+CD69+ CD8+ T‐cells through programmed cell death‐ligand 1 (PD‐L1)

Abstract: IntroductionPrevious work from our laboratory has demonstrated in vivo persistence of CD103+CD69+ brain resident memory CD8+ T‐cells (bTRM) following viral infection, and that the PD‐1: PD‐L1 pathway promotes development of these TRM cells within the brain. Although glial cells express low basal levels of PD‐L1, its expression is upregulated upon IFN‐γ‐treatment, and they have been shown to modulate antiviral T‐cell effector responses through the PD‐1: PD‐L1 pathway.MethodsWe performed flow cytometric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Recent in vitro studies have identified a role for activated microglia in promoting generation and retention of bT RM . In these studies, upregulation of CD69, CD103, and CD127 on CD8 + T cells was noted in the presence of glial cells (66). Additionally, blocking of PD-L1 on glia led to decreased expression of CD103, and CD127, on CD69 + CD8 + T cells.…”
Section: Establishment Of T Rm Within Brainmentioning
confidence: 81%
See 4 more Smart Citations
“…Recent in vitro studies have identified a role for activated microglia in promoting generation and retention of bT RM . In these studies, upregulation of CD69, CD103, and CD127 on CD8 + T cells was noted in the presence of glial cells (66). Additionally, blocking of PD-L1 on glia led to decreased expression of CD103, and CD127, on CD69 + CD8 + T cells.…”
Section: Establishment Of T Rm Within Brainmentioning
confidence: 81%
“…In brain, the majority of persisting CD8 + T cells co-express CD103 and CD69 (10,67). Local conversion of brain-infiltrating CD8 + T cells to a CD69 + CD103 + population has been reported in various disease settings (10,12,66,89,90). CD103 functions through aiding in tissue retention through interaction with BRAIN-RESIDENT T CELLS FOLLOWING VIRAL INFECTION E-cadherin, which has been well established in epithelial cells (14,15).…”
Section: Establishment Of T Rm Within Brainmentioning
confidence: 99%
See 3 more Smart Citations